Barriers and Solutions in Nursing Roles: Perspectives of Nursing Students and Academics - Arzu Çağla Avcı; Fatih Özdemir; Eslem Gönen; Begüm Kırık; Işıl Işık (Turkish Journal of Health Science and Life, 2026)
This study aimed to examine the barriers that nurses encounter in fulfilling their professional roles and to explore solution-oriented suggestions through a phenomenological approach. Nursing is a discipline that encompasses multifaceted professional roles such as caregiver, educator, advocate, researcher, manager, and decision-maker. However, performing these roles effectively can be challenging for nurses due to various barriers arising at individual, institutional, and societal levels. The research was conducted with 18 participants, including nursing students and faculty members from a foundation university. Data were collected through semi-structured in-depth individual interviews and analyzed using thematic analysis. The findings were categorized under five main themes: individual-level barriers (e.g., lack of motivation, low self-confidence, language barriers), institutional-level barriers (e.g., excessive workload, staff shortages, lack of merit-based management), societal-level barriers (e.g., stereotypes, low professional prestige), role-specific implementation difficulties, and participant-suggested solutions. Participants emphasized the need for enhanced educational opportunities, stronger managerial support, increased public awareness, and institutional encouragement for professional development to improve the implementation of nursing roles. This study sheds light on the multidimensional nature of the barriers faced by nurses and, with its solution-oriented perspective, is expected to contribute to both health policy and nursing education.